Epidemiology and molecular characterization of CTX-M-type ESBLs producing Escherichia coli isolated from clinical settings - Keyi Yu; Zhenzhou Huang; Yue Xiao; Xuemei Bai; He Gao; Duochun Wang (Journal of Global Antimicrobial Resistance, 2024)
ABSTRACT: Objectives: Recently, blaCTX-Ms have become the dominant ESBLs for E. coli strains worldwide. We aim to provide a systematic study on the relationships between sequence types (STs), clinical origins, and the blaCTX-Ms genotypes of E. coli strains. Methods: Totally, 1005 complete sequences of clinical E. coli were collected from NCBI. Multilocus sequence typing (MLST) and antibiotic resistance genes screening were performed. Results: Faeces (26.27%), urine (16.02%), and blood (8.26%) were shown to be the main sources of clinical E. coli isolates. The isolates belong to 153 STs and 26 clonal complexes (CCs). The most prevalent STs were ST2 (11.3%), ST43 (8.6%), and ST8 (5.7%). The positive rate for blaCTX-Ms was 34.7%. Different samples showed significantly different blaCTX-Ms positive rates (P<0.05). The main genotypes were blaCTX-M-55-like (47.6%), blaCTX-M-1-like (31.8%), and blaCTX-M-2-like (22.1%). The majority of ST2 strains had blaCTX-M-55-like genes. In ST8 strains, there was a homogeneous distribution of blaCTX-M-9, blaCTX-M-65, blaCTX-M-55, blaCTX-M-2, and blaCTX-M-1. Only ST43 strains exhibited the presence of blaCTX-M-79. The blaCTX-Ms showed a pattern of cross-continental transmission with intra-regional spread. Among the 349 blaCTX-Ms-producing E. coli strains, 148 strains also carried carbapenem resistance genes, including blaNDM (119, 34.1%), blaKPC (16, 4.6%), blaOXA-48 (9, 2.6%) and blaIMP (4, 1.1%). Also, 81 strains carried the mcr gene (23.2%). Conclusions: E. coli has become increasingly rich in blaCTX-Ms genotypes. Our findings about the connection between E. coli STs and blaCTX-Ms can be utilized to identify E. coli strains with high potential to spread drug resistance in the future.